Recent geomorphic evolution of the fan delta of the Mornos river, Greece: natural processes and human impacts - Karymbalis, E.; Gaki-Papanastassiou, K.; Maroukian, H. (Bulletin of the Geological Society of Greece, 2007)
The Mornos river fan delta is located on the northern side of the western Gulf of Corinth is a Gilbert-type fan delta with an arcuate form characterised by the abundance of coarse sediments. In order to determine the processes which contributed in the configuration of the fan delta during the last two centuries a detailed geomorphic map was prepared depicting both the deltaic plain and the coastal zone features. Comparative examination of 1945, 1986 and 1998 aerial photographs and reliable maps of the last two centuries along with field observations detected recent changes of the fan delta. The construction of a dam in the upper reaches of the basin in 1980 has significantly decreased the sediment supply downstream and has slackened the growth of the fan delta. After 1980 the eastern distributary has been abandoned causing a 120 m retreat at the river mouth. Although a progradation rate of 4 m/year has been observed for the western active distributary in the period between 1945 and 1986, no remarkable changes have occurred since that period. Additionally, an assessment of the impact of the potential global future sea-level rise to the fan delta is attempted.